Comparative study on WRF model simulations from the viewpoint of optimum ship routing. (1st July 2020) - Chen, Chen; Sasa, Kenji; Ohsawa, Teruo; Prpić-Oršić, Jasna
Abstract: In addition to other studies focused on the WRF performance of rainfall, temperature, and precipitation, the present study provides practical suggestions for ship operators on choosing grid point value (GPV) datasets and WRF modeling approaches to help make better decisions on weather routing by estimating strong wind with a higher accuracy. Two different GPV datasets, the NCEP-FNL and ERA-Interim, are used for WRF modeling. Various modeling approaches, which include applying different physics options and choosing whether to adopt the four-dimensional-data-assimilation, are employed for numerical simulation. Then, on-board measurements of a bulk carrier has been used to validate the calculated wind of eight rough-sea navigational cases. This occurs over a wide spatial range, covering ocean regions such as the Northwest Pacific Ocean, South of Australia, Tasman Sea, Southeast of Africa, and Southeast of America, as well as a wide temporal range of four years. Results of 64 WRF simulations show that ERA-Interim is suitable for longer periods, while NCEP-FNL can analyze extremely high winds. Additionally, grid nudging can also reduce the wind strength due to its smoothing effect. Finally, selections of these different GPV datasets and modeling approaches for ship weather routing are discussed, particularly for rough-sea navigations. Highlights: Ocean surface wind over rough seas of several seasons and ocean regions have been generated. GPV datasets including both the NCEP-FNL and ERA-Interim have been utilized for wind simulation. On-board observations of weather and ship motion has been done for a long term. Modelling approaches can add significant value to optimum ship routing.